Body and Sexuality in the Struggle for Recognition: The Nature-Nurture Debate in a New Social Imaginary - Di Nicola, Paola (Italian Sociological Review, 2023)
The claims made by all social groups who do not identify with the dominant model of heteronormativity can be framed within the broader context of struggles for the recognition of cultural and identity rights pertaining to their sexuality. Such demands conform to Hegel’s classic pattern of recognition, later reworked by Honneth, with identity struggles that are variously private (construction of the self, self-confidence), public (self-worth, legal recognition) and community-based (respect for cultures epitomising a certain way of life). With their aim of enabling a just life to coexist with a good life, these claims enter the realm of communitarian theories. Indeed, despite the strong emphasis on safeguarding individual and subjective rights, a communitarian element is apparent inasmuch as these movements demand “different” laws to protect “different” subjects. Recognition and respect for diversity are embedded in the new narrative championed by neo-communitarians, which requires fragmentation of the legal system in order to take consistent shape. This article highlights the techniques which many of these groups have adopted in an attempt to avoid this drift towards communitarianism. In so doing, they have transcended the debate on nature (biology) and nurture (cultural norms) by creating a new narrative of body and sexuality which rejects the idea of biological difference and transforms their cultural diversity into a new normative order. Throughout history, narratives, social imaginaries, myths, traditions, and institutions have been built around the transformative process of male and female babies becoming men and women. These have shaped interpersonal relations between the sexes at every level of social reality. One essential element of the challenge posed by those fighting for the recognition of sexual rights is the creation of new narratives and a new social reality.